2011
DOI: 10.7205/milmed-d-10-00202
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Screening in Children With Wartime-Deployed Parents

Abstract: Children of U.S. military families are exposed to unique challenges and stressors directly related to their parents' wartime deployments, potentially placing them at higher risk for psychosocial disruption. The objective of this study was to investigate the effects of parental wartime military deployment on psychosocial symptoms as measured by parent and youth self-report on the Pediatric Symptom Checklist. During annual physicals at a large military pediatric clinic, parents (216) and youth (198) were surveye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 20 publications
1
42
0
1
Order By: Relevance
“…family members increased. Among parents and youth surveyed during annual physicals in a military pediatric clinic, current parent deployment was associated with more child psychosocial symptoms, including greater internalizing symptoms, externalizing symptoms, school problems, and attention problems (Aranda et al 2011). School staff in military-connected schools also reported that deployments may be associated with increased child anxiety (Chandra et al 2010b).…”
Section: Current Eramentioning
confidence: 99%
“…family members increased. Among parents and youth surveyed during annual physicals in a military pediatric clinic, current parent deployment was associated with more child psychosocial symptoms, including greater internalizing symptoms, externalizing symptoms, school problems, and attention problems (Aranda et al 2011). School staff in military-connected schools also reported that deployments may be associated with increased child anxiety (Chandra et al 2010b).…”
Section: Current Eramentioning
confidence: 99%
“…Adolescents self-report problems with a similar prevalence as their parents and may have more valid reporting than their parents of their own internalizing symptoms. 38 …”
Section: Suggestions For Pediatriciansmentioning
confidence: 99%
“…38 In a telephone survey of 1500 military youth and their at-home parent, Chandra reported increased emotional difficulties associated with longer deployment times and emphasized the importance of positive coping and mental health of the at-home parent. 8 The effects of war can have life-threatening consequences for military children and their families far removed from the battlefields.…”
Section: Adolescentsmentioning
confidence: 99%
See 2 more Smart Citations